Research on strategies to enhance the effectiveness of financial information dissemination under the background of rural revitalization - Song Qinyu; Xi Zhuang (International Journal of Communication and Society, 2023)
This paper aims to put forward optimization strategies for the shortcomings of rural financial information dissemination, so as to improve the effectiveness of financial information dissemination in rural areas，so as to form a win-win situation of two-way financial information interaction between rural commercial banks and farmers, stimulating rural development. Under the background of rural revitalization, financial information dissemination can help financial enterprises establish brand image and promote financial products and services, which plays a significant role in getting through the "last mile" of Inclusive finance. At present, facing the dual effects of policy environment and market environment, banks and other financial institutions are altering their focus and continuously increasing the dissemination of rural financial information. However, due to the influence of multiple factors such as regional environment and audience characteristics, related products, services and financial knowledge have not been fully, sufficiently and effectively disseminated. This paper takes the communication behavior of farmers and rural commercial banks in Jiangsu as the research object.In order to integrate into consumers' life and understand consumers' exposed or potential needs, we analyze the characteristics of information communication and audience in rural areas in the form of questionnaire and written interview, and put forward targeted optimization strategies according to the problems and difficulties existing in the current actual communication, so as to improve the effectiveness of financial information communication.The innovative feature of this paper is to carry out interdisciplinary research, cross integrate the theories of Journalism and communication and finance, and apply the information communication theory in journalism and communication to the field of finance.